The prevalence of Tramadol abuse and associated factors among Hawassa University students, Hawassa, Ethiopia - Adanech Shifarew Legasse; Wudinesh Tamiru; Fatiya Mohammed; Getu Ataro (PLoS ONE, 2025)
Introduction Tramadol abuse is a current public health concern in Ethiopia. Drug abuse including that of tramadol is a significant public health issue that causes health, economic, and social problems to individual drug users, their families, the community, and the entire nation. Therefore this study delivers information regarding current tramadol abuse among students of an Ethiopian University. Objective The aim of this study is to assess the prevalence of tramadol abuse and associated factors among Hawassa university students, February to June 2023. Methods and materials A cross-sectional study was performed among 402 randomly selected Hawassa university students. Data was collected from participant through self-administered researcher made questionnaire using kobo toolbox software applications. Data from kobo toolbox were directly exported to and analyzed by using SPSS version 26 software. Binary logistic regression was applied to identify the factors associated with tramadol abuse. In the final model, Adjusted Odds Ratio, and 95% CI was used to measure the strength of association and P-value less than 0.05 considered statistically significant. Result A total of 402 students were enrolled in this study of which 46 students (11.4%) [95% CI 8.5–14.7] had history of tramadol abuse once in their lifetime with 23.9% of them were active tramadol abuser with some dependence behaviors. The result of multivariate analysis shows that having a friend who use drugs [AOR = 1.691, 95% CI (0.718–3.980), p = 0.041], knowing about tramadol [AOR = 13.766, 95%CI (3.003–63.113), p = 0.001] and having the history of taking tramadol with physicians prescription in their life time [AOR = 7.960, 95%CI (3.603–17.587), P < 0.001] were the significant predictors of tramadol abuse. Conclusion The life time prevalence of tramadol abuse among university students is high and it demands attention of government and the general public.